Eksistensi Radika.FM sebagai Radio Publik di Majalengka - Titih Nurhaipah; Syamsul Arif Billah (Universitas Informatika dan Bisnis Indonesia, 2023)
Radika 100.3FM is a public radio station owned by the local government of Majalengka Regency. The broadcast content format is in the form of information about Majalengka district. Radika FM is present as a source of information and communication between the community and the government. Apart from functioning for the dissemination of information, there are also broadcast programs that function as education and entertainment. The purpose of this research is to find out the existence of broadcasting radio owned by the local government of Majalengka Regency as a medium for public disclosure information as well as a reference source of information for the community. The research approach uses qualitative, the form of presentation comes from the findings that are processed and interpreted. With data collection techniques including interviews, observation and documentation. The results of this study are that Radika FM has the main task of overseeing every policy and development of the Majalengka Regency local government so that information transparency occurs. In addition, in order to renew through the launch of the Radika.FM APK on the android system so that all Radika FM listeners can be accessed easily, cheaply, and quickly. This is a long process to continue to air and compete in the era of industry 4.0.